Kajian Nilai Pendidikan Agama Hindu Dalam Fragmentari Katundung Sita Pada Pesta Kesenian Bali Ke 38 Tahun 2016 - Nengah Adi Widiastrawan; I Ketut Sudarsana; Ida Ayu Adi Armini (Jayapangus Press, 2019)
The preservation of art and culture in Bali, especially performing arts, has seen a lot of development since the idea of the Bali Arts Festival, the Bali Arts Festival held by the Bali Provincial government and the Balinese Community, is a public space and creativity event for Balinese performing artists to showing their best works of art. In the 38th Bali Arts Festival in 2016, Institut Hindu Dharma Negeri Denpasar performed a Fragmentary story with the title Katundung Sita which is based on the Mahabharata story. This Fragmentary tells about how was the exile of Dewi Sita in the middle of the forest by the Rama because hearing the people of Ayodhya Pura did not believe about the loyalty of Dewi Sita who has long been locked up in the Kingdom of Alengka by Rahwana. This research shows, (1) the staging structure in Fragmentari Katundung Sita can be divided into 6 parts, there are: 1. Prologue, 2. Chapter I, 3. Chapter II, 4. Chapter III, and 5. Chapter IV, and 6. Fragmentari’saccompaniment of Katundung Sita (2) The meaning inFragmentari Katundung Sita 1. As a preserver of culture or as a process of preserving culture that has been inherited by the ancestors especially in dance performances, 2. The harmonization of balance in the staging of Fragmentari Katundung Sita reflects life and balance between microkosmos and macrokosmos, 3. Aesthetics is the whole form of Fragmentari Katundung Sita which means beauty. (3) The value of Hindu religious education inFragmentariKatundungSita 1. The value of Nitisastra education which inFragmentari Katundung Sita that contains the concept of AstaBrata 2. The value of Ethics education which is in the performance it was found that as a leader or being a leader, people should be able to carry out the ethics as a leader who is able to control the characteristics that exist in him based on the concept of AstaBrata.